Unions and Learning in a Global Economy: International and Comparative Perspectives - Sawchuk, Peter H. (Labour / Le Travail, 2003)
The article reviews the book "Unions and Learning in a Global Economy: International and Comparative Perspectives," edited by Bruce Spencer.
Keywords: BOOKS – Reviews; Labor economics; Nonfiction; SPENCER; Bruce; UNIONS & Learning in a Global Economy: International & Comparative Perspectives (Book)